Production and Biomass of Pokea Clam (Batissa violacea var. celebensis von Martens, 1897) in the Langkumbe River Waters North Buton Southeast Sulawesi - Tri Abdul Rahman; Bahtiar Bahtiar; Pramono Hery Santoso (Jurnal Moluska Indonesia, 2021)
Langkumbe River is located in West Kulisusu District and has long been used by the community for various daily activities. One of the resources often used by the people around Langkumbe River is pokea clams. The aim of this study was to determine the production and biomass of pokea clams (B. violacea) in Langkumbe River Waters of North Buton Regency from August to October 2017. The sampling method used was swept area method using a traditional fishing gear "Tangge" (fishing gear). The samples were measured for the length, width and thickness.  The total weight was measured with the clam/total mass (MT) and the weight of the meat. The samples were dried using an oven for 24 hours at 70 °C to obtain the shell-free dry mass (SFDW). Data were analyzed using standard formulas. The total sample obtained was 1.307 individuals. The highest density of pokea clam was found in August at 596.8 ind/m². Annual production of pokea clam (B. violacea) in Langkumbe River with a total annual production of 1,107.33 gSFDW/m2/year. The highest and lowest production are 297.09 gSFDW/m²/year at size 2.19-2.54cm and -0.16 gSFDW /m²/year at size 4.70-5.05cm, respectively. The total population biomass was 528.03 gSFDW/m2 with the highest biomass 171.72 gSFDW/m²/year at size 2.55-2.90 cm and the lowest was 1.40 gSFDW /m²/year at size 4.70-5.05 cm, so that the recovery rate (P/B ratio) was 2.1 gSFDW/m2/year.